Global benchmarking of block caves: a super cave update - Mawdesley, C; Altankhuu, B (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
Over the past two decades, block caving has been applied at greater depths and to significantly taller draw columns and with a substantial increase in scale and productivity. Historic benchmarking does not capture the operational characteristics of the deeper, taller caves that reached peak production after 2003, nor the first cohort of super caves (caves with lift heights >300 m and production rates >70 ktpd) that were at the project stage 20 years ago. There are currently 7 super caves (i.e. design capacity >70 ktpd) either at peak production, in ramp-up or forecast to reach peak production in the early to mid-2030s. Rio Tinto recently undertook a benchmarking analysis of global block caves using only public sources to supplement in-house caving experience and capture developments in these deeper, taller caves over the past 20 years. This paper presents the results of the benchmarking study and summarises the current state of block caving, with emphasis on the super caves and deep block caves commissioned since 2003. Hugo North Lift 1 in Oyu Tolgoi, Mongolia, provides the primary reference point for scale and depth, with the focus on deep, large caves. However, since the number of super caves is limited, the benchmarking also drew explicitly on smaller, deep block caves of comparable footprint scale and production to Hugo North Panel 0, the first cave mined at Oyu Tolgoi. All information presented in this paper, including for Oyu Tolgoi, is publicly available.
Keywords: benchmarking; block cave; super cave; caving; Oyu Tolgoi; Hugo North